Effect of climate factors on survival and growth of planted trees in scots pine (pinus sylvestris l.) plantations - G, Batsaikhan; P, Battulga; J, Baterdene; S, Gerelbaatar; J, Tsogtbaatar (Mongolian Journal of Agricultural Sciences, 2019)
This study was conducted in planted forests located in the Tujyin Nars National Park territory of Selenge province, Mongolia. We aimed at studying the effect of climate factors on seedling survival and tree growth at the Scots pine plantations. A total of five 50 x 20 m (0.1 ha) sized square sample plots were established at the plantations, planted between 2003 and 2007. All field measurements and data collection were carried out annually in September and October between 2003 and 2017. Annual field measurements of seedlings included: tree health status, diameter at stem basis, total height and annual height increments. We used climate data taken from the closest meteorological station (8-15 km to the north-west), “Sukhbaatar” located in Sukhbaatar Soum of Selenge province. To calculate the statistical analysis of the survival rate and seedling growth, we used the one-way analysis of variance (ANOVA) method to determine statistically significant differences in means among variables between the sites. An F-test and Pearson's correlation coefficient were used to assess the relationships between climate variables and survival and tree growth. Our findings showed a significant difference (F=28.4, p<0.001) between seedling survival among plantations planted in different years of plantation establishment. The study revealed that there is a strong negative correlation (r=-0.76) between seedling survival and number of critical dry days, and contrary, strong positive correlation (r =0.71) with the precipitation for May. The increment of planted trees was more sensitive to air temperature (r = 0.47), annual rainfall (r = 0.72), air relative humidity and number of dry days during the first three years than in subsequent years. Таримал өсвөр нарсан (pinus sylvestris l.) ойн амьдралт, өсөлтөнд уур амьсгалын үзүүлэх нөлөө Хураангуй Тус судалгааг Сэлэнгэ аймгийн Алтанбулаг, Шаамар сумын нутагт ойжуулалтаар тарьж ургуулсан таримал нарсан ойд гүйцэтгэв. Судалгааны ажлын зорилго нь таримал ойн моддын амьдралт, өсөлтөнд уур амьсгалын үзүүлэх нөлөөг судлахад оршино. Судалгаанд 2003-2007 онуудад ойжуулсан таримал ойн мониторинг судалгааг 2003 -2017 онуудад жил бүр тасралтгүй гүйцэтгэлээ. Ойжуулсан талбай бүрд 50 х 20 м (1000 м2) хэмжээтэй дээж талбайг байгуулан, түүнд таримал модны эрүүл байдал, ишний өндөр, диаметрийн өсөлт болон титмийн өндрийг хэмжив. Ишний шинжилгээний дээжид модны өндрийн болон диаметрийн өсөлтийн хэмжилтийг хийсэн ба уур амьсгалын үзүүлэлтэд судалгааны талбайд хамгийн ойр (10 км) орших Сэлэнгэ аймгийн цаг уурын ажиглалтын “Сүхбаатар” станцын 2003-2017 оны хугацаанд дахь цаг уурын мэдээг ашиглав. Хэмжилтийн статистик үзүүлэлтүүдийг боловсруулахад нэг хүчин зүйлт вариансийн шинжилгээ (ANOVA), модны өндөр, диаметрийн өсөлтийн явц болон уур амьсгалын үзүүлэлтүүд хоорондын хамаарлыг Персоны корреляцын коэффициеитээр илэрхийлэв. Судалгааны үр дүнгээс үзвэл, ялгаатай цаг хугацаанд ойжуулсан талбайн моддын амьдралт статистикийн хувьд ялгаатай (F=28.4, p<0.001), ялангуяа 5-р сарын хэт хуурайшилттай өдрийн үргэлжлэх хугацаа (r=-0.76), ургамал ургалтын хугацааны агаарын температур, хур тунадасны нийлбэр (5-р сар r =0.71, 6- сар r=0.41, 7- сар r= 0.46) - тэй хүчтэй, эерэг хамааралтай байна. Ойжуулалтанд шилжүүлсний дараах тарьцын хоёр болон гурав дахь жилийн нийлбэр өндрийн өсөлт, жилийн дундаж агаарын температур (r = 0.47), диаметрийн өсөлт нь жилийн нийлбэр хур тунадастай (r = 0.72) эерэг, хүчтэй хамааралтай байна. Түлхүүр үг: Ойжуулалт,өндөр, диаметр, цаг уур, хамаарал